STUDY OF THE PHYSICO-CHEMICAL PROPERTIES OF OLIGOMERS BASED ON EPICHLORHYDRIN - M. E, Toshev; B. A, Normurodov; Kh. Kh, Turaev; N. Zh., Pardaeva (Miasto Przyszłości, 2023)
The purpose of this work is the synthesis and study of Thiokol oligomer (EAF-9) based on sodium polysulfide, epichlorohydrin, and ammonium phosphate, intended for use as the main component of Thiokol sealing substance. To achieve this goal, a thiokol oligomer based on sodium tetrasulfide, epichlorohydrin, and ammonium phosphate was studied and the optimal conditions for the synthesis of a thiokol oligomer were determined. The influence of the molar ratios of starting materials on the composition and physicochemical properties of the synthesized Thiokol oligomer has been studied. The temperature of the optimal polycondensation reaction was equal to 80°С, the reaction time was 1.5–2 h, and the yield of the target product reached 94%. The thiol oligomer with the best efficiency was obtained at a molar ratio of sodium tetrasulfide, epichlorohydrin, and ammonium phosphate of 1:1:1, respectively. Based on the results of IR spectroscopy and differential scanning calorimetry, a reaction for the formation of a thiokol oligomer was proposed.